A study on the CAPM and its extensions in perceptive of Pakistani asset management organisations. (9th August 2020) - Ashfaq, Saleha; Tang, Yong; Maqbool, Rashid
This paper explains about the capital asset pricing model (CAPM), its capability and its implication in the real-world data. To crave this thirst, we form this study by using the earlier CAPM approaches (Lintner, 1965; Sharpe, 1964) that are also employed by many latest researches. Though there is a lot of literature available on the extensions of the CAPM, still there is no consensus in the literature with respect to what a reasonable proportion of risk is, and therefore, regarding what is an appropriate measure for assessing risk-adjusted performance. Along these lines, the mission for robust asset pricing models proceeds. Owed to this, we chose five asset managing organisations for the Pakistani stock market KSE 100 Index for the time period of 2012 to 2015. We also employed descriptive test and robust test ratio on our selected data. The finding of the research shows a significant result and suggested the good performance of assets management organisations.